Optimization of a high-pressure microwave curing process for T800/X850 carbon fiber-reinforced plastic. (February 2020) - Guan, Chenglong; Zhan, Lihua; Liu, Guiming; Yang, Xiaobo; Dai, Guangming; Jiang, Chengbiao; Chen, Xiaoping
Compared with the conventional composite curing processes, high-pressure microwave curing is a promising technology. In this study, a set of devices for high-pressure microwave curing was built and equipped with real-time temperature measurement capability and a microwave input control system. The orthogonal experimental method was applied to optimize three process parameters, including the heating rate, curing temperature, and holding time, for the high-pressure microwave curing of T800/X850 composites. The effects of the three parameters on the curing quality were studied by measuring the interlaminar shear strength (ILSS) and conducting differential scanning calorimeter tests. The fracture surface of the samples was also examined by scanning electron microscopy. The results showed that the heating rate had a significant effect on the ILSS of the laminates, and the degree of cure of all samples was more than 95% in the tests. Furthermore, the optimal process parameters were determined as follows: heat up to 170°C with a heating rate of 6°C min −1 and a holding time of 90 min. The total curing time of the sample was 42.4%, and the ILSS of the sample was slightly enhanced by 0.31% compared with standard thermal curing. These results could serve to make trade-offs between reducing manufacturing time and preserving the mechanical properties of microwave-cured composites.